Repatriation of Corporate Executives: An Empirical Study - Harvey, Michael G. (Journal of International Business Studies, 1989)
The effective management of corporate executives returning from foreign assignments has received little attention from academic researchers. This study is based on questionnaires completed by members of the American Society of Personnel Administration: International (ASPI). The focus of the study was directed at problems that occurred in repatriating executives, programs used by corporations to repatriate returning executives, and examines why programs have not been instituted by multinational corporations.